Manajemen Kurikulum pada Lembaga Islam - Teguh Teguh (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine curriculum management in Islamic educational institutions in addressing the challenges of modernization and digitalization without abandoning Islamic values. The research background is based on the reality that many Islamic institutions still face obstacles in curriculum management, including knowledge integration, technological readiness, and teacher competence. The study employs a qualitative approach with a case study method conducted at Madrasah Tsanawiyah and Aliyah Salafiyah of Pondok Pesantren Al-Hikmah Yogyakarta. Data collection techniques include interviews, observations, and documentation, analyzed using Miles and Huberman’s model. The findings reveal that the institution has implemented integrative and participatory curriculum management by combining the National Curriculum with local pesantren content. The curriculum is developed through teacher deliberations, implementation based on Islamic values in all subjects, and periodic evaluation. Although challenges remain, such as teacher competency variation and suboptimal character evaluation, this model demonstrates relevant adaptation to the demands of the 21st century. The study’s implications contribute to the development of holistic, contextual, and Islamically-characterized curriculum management strategies in Islamic educational institutions.